Understanding the transition between Marx's Capital I and II. Issue 2 (3rd July 2022) - Friedenthal, Tomás
Abstract : In the literature concerning Marx's Capital II, the question of its systematic connection with Capital I has received limited attention. The present paper is an attempt to fill this gap. Tracing the widening contradictions between capital as it manifests itself in circulation and capital in production, as well as between the total social capital and individual capital, contradictions that transpire as the investigation of the process of production of capital unfolds throughout Capital I, the paper shows that their solution depends on research proceeding forwards from production to the realm of circulation. This already provides a subjective justification for the transition between Capital I and II, but it does not yet grasp the actual necessity that capital itself follows as the actual subject of the movement of our present process of metabolism as human beings. The paper then goes beyond that subjective point of view to show why and how capital necessarily prompts itself forward from the realm of production into the cycle which constitutes the circulation of capital.